Demand estimation and consumer welfare in the banking industry - Dick, Astrid A. (Journal of Banking & Finance, 2008)
This paper estimates a structural demand model for commercial bank deposit services in order to measure the effects on consumers given dramatic changes in bank services throughout US branching deregulation in the 1990s. Following the discrete choice literature, consumer decisions are based on prices and bank characteristics. Consumers are found to respond to deposit rates, and to a lesser extent, to account fees, in choosing a depository institution. Moreover, consumers respond favorably to the branch staffing and geographic density, as well as to the bank’s age, size, and geographic diversification. Consumers in most markets experience a slight increase in welfare throughout the period.